用因式分解解方程 , 要过程

来源:百度知道 编辑:UC知道 时间:2024/06/16 01:32:32
2(X-3)^2=X^2-9

2(X-3)^2=X^2-9
2(x^2-6x+9)=x^2-9
2x^2-12x+18-x^2+9=0
x^2-12x+27=0
(x-3)(x-9)=0
x=3或9

解: 2(X-3)^2=(X+3)(X-3)
2(X-3)=(X+3)
2X-6=X+3
X=9

2(X2-6X+9)=X2-9
2X2-12X+18=X2-9
X2-12X+27=0
(X-3)(X-9)=0
X=3或X=9

2(X-3)^2=X^2-9
2(X-3)(X-3)-(X-3)(X+3)=0
(X-3)[2(X-3)-(X+3)]=0
(X-3)(2X-6-X-3)=0
(X-3)(X-9)=0
X=3 OR 9

2(X-3)^2=X^2-9
2(X-3)(X-3)=(X-3)(X+3)
2(X-3)(X-3)-(X-3)(X+3)=0
(X-3)[2(X-3)-(X+3)]=0
(X-3)(X-9)=0
X=3或9

解:2(X-3)^2=X^2-9
2(X-3)^2=(X-3)*(X+3) 移项得
(X-3)[2(X-3)-(X+3)]=0
(X-3)*(X-9)=0
解得X=3或9